Microbiological Analysis of Indoor Air in Selected Primary Schools: Health Concerns and Recommendations - Muhammad, Shamsudeen Muhammad (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
The quality of indoor air in various buildings is crucial for maintaining the health and well-being of individuals. Exposure to airborne microorganisms can have detrimental effects on respiratory health. This study aimed to evaluate the microbiological quality of indoor air in selected primary schools in Aliero, Nigeria. Three primary schools were randomly chosen, air samples were collected using settle plates. Petri dishes containing different culture media were exposed twice daily (morning and noon). The number of organisms per cubic meter of air (CFU/m³) was recorded, and standard microbiological methods were used to identify bacterial and fungal isolates. The study revealed a wide range of bacterial and fungal contamination in classroom environments. Bacterial loads ranged from 543-165 CFU/m³, while fungal loads ranged from 146- 32 CFU/m³. Four bacterial species and five fungal genera were identified. The bacteria included Bacillus spp, Proteus spp, Staphylococcus aureus, and Micrococcus spp, while the fungal genera isolated included Aspergillus spp, Mucor spp, Fusarium spp, Penicillium spp, and Rhizopus spp. The most prevalent bacteria were Bacillus spp (34.38%) and Micrococcus spp (28.13%), while the most frequently isolated fungi were Fusarium spp (36.36%) and Penicillium spp (33.33%). The finding of this study has shed light on the indoor air quality of selected primary schools in Aliero. The present study also revealed the microbial diversity as well as the frequency of occurrence of various isolates. Measures such as improved ventilation, stringent cleaning protocols, and regular monitoring to ensure a healthier indoor environment for both students and staff.